Baseline Glomerular Filtration Rate and Cisplatin- Induced Renal Toxicity in Urothelial Cancer Patients - Loh, Janice M. (Clin Genitourin Cancer, 2017)
Cisplatin’s nephrotoxicity limits its use in patients with renal insufficiency. In our study of 81 urothelial cancer patients treated with cisplatin, those with glomerular filtration rate (GFR) < 60 mL/min did not experience a greater decline in renal function compared to patients with GFR ≥ 60 mL/min. These findings may support extending the option of cisplatin-based therapy to previously ineligible patients. BACKGROUND: Cisplatin eligibility for clinical trials has been defined as glomerular filtration rate (GFR) ≥ 60 mL/min due to the risk of nephrotoxicity in patients with renal impairment. For urothelial cancer, substitution of carboplatin instead of cisplatin compromises outcomes. We evaluated change in GFR in patients treated with cisplatin despite baseline GFR < 60 mL/min to determine risk of nephrotoxicity. PATIENTS AND METHODS: Patients treated between 2009 and 2014 at our institution were identified by the institutional review board—approved cystectomy database. GFR percentage change was compared by age (< 75 vs. ≥ 75 years), pretreatment GFR (< 60 vs. ≥ 60 mL/min), therapy setting (neoadjuvant, adjuvant, or metastatic), primary disease site, and comorbidities (diabetes, hypertension, and hyperlipidemia). The associations between overall survival and age or GFR were also assessed. RESULTS: There were 81 patients who received cisplatin-based therapy and whose pre- and posttreatment GFR were available. Median GFR change was −1.6% for patients with pretreatment GFR < 60 mL/min compared to −10.9% for patients with pretreatment GFR ≥ 60 mL/min (P = .17). Therapy setting was the only factor in our study to be significantly associated with GFR change (P = .027). No association was found between overall survival and pre- or posttreatment GFR, GFR percentage change, or age. CONCLUSION: Our data support the hypothesis that urothelial cancer patients with GFR < 60 mL/min do not experience a greater decline in renal function after cisplatin compared to patients with GFR ≥ 60 mL/min. If validated, this may extend the option of cisplatin-based therapy to previously ineligible patients.